KOMUNIKASI PERSUASIF TENAGA PEMASAR DALAM MENARIK MINAT NASABAH: (Studi kasus di PT. Asuransi Jiwa Sequis Life Cabang SEV3N Kota Solo) - Ayu Purnomo, Klara (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This research aims to describe the application of persuasive communication carried out by PT marketers. Sequis Life SEV3N Solo City Branch in influencing customers' decisions to buy life insurance products. The focus of this research is to understand the persuasive communication used by marketers and its impact on the ongoing persuasion process. Persuasive communication is an effort made to influence other people in making decisions, in this case the decision to choose and buy insurance products. The method used in this research is a qualitative approach with data collection techniques through in-depth interviews and observation. The research results show that the marketing staff of PT. Sequis Life Sev3n Solo City Branch uses various persuasive communication techniques, such as using a personal approach, conveying clear and convincing information, and using appropriate communication to build closer relationships with customers. Apart from that, the confidence and trust factor built through effective communication is also an important element in increasing sales figures for insurance products. It is hoped that this research will provide insight into effective persuasive communication in the life insurance industry and become a reference for other insurance companies that want to improve performance.